Pengelompokan Genotipe Jarak Pagar Berdasarkan Ketahanannya terhadap Kekeringan pada Fase Pembibitan di Lahan Pasir Pantai - I Gusti Made Arya Parwata; Didik Indradewa; Prapto Yudono; Bambang Djadmo Kertonegoro (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2010)
Extension of jatropha planting on coastal sandy soil is an effort to look for an alternatif area to other soil types, this experiment is one of a series experiment aiming to classify jatropha based on their drought resistance, and to determine watering interval causing drought stress. The experiment was arranged using Split Plot Design with watering interval (once in 1, 3, 5, 7, and 9 day (s)) as main plot, and jatropha genotypes (IP-1A, IP-1M, IP-1P, IP-2A, IP-2M, IP-2P, Unggul Lokal (NTB), Gundul and Daun Kuning) as sub plot. The seeds of genotypes were planted in black polybag with coastal sandy soil media. The parameters observed were plant height, stem diameter, number of leaf, leaf width and plant dry weight, and the data collected were analyzed using Analysis of Variance, DMRT, Regrression and Cluster Analysis. The result showed that IP-1A, IP-2M, Gundul and IP-1M are the resistant genotypes, whereas Unggul Lokal, Daun Kuning, IP-2A and IP-2P are the susceptible genotypes. Once in one and three day (s) are optimum watering intervals, and once in nine days is a watering interval causing drought stress. Keywords : jatropha, drought, watering, coastal sandy soil